Increased Epicardial Adipose Tissue Thickness is Associated With Angiographic Thrombus Burden in the Patients With Non-ST-Segment Elevation Myocardial Infarction. (October 2015) - Bakirci, Eftal Murat; Degirmenci, Husnu; Duman, Hakan; Inci, Sinan; Hamur, Hikmet; Buyuklu, Mutlu; Ceyhun, Gokhan; Topal, Ergun
We aimed to evaluate the relation among epicardial adipose tissue (EAT) thickness, angiographic presence of thrombus, and the no-reflow in the patients with non-ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention. The study population consisted of 229 patients. The EAT thickness and neutrophil to lymphocyte ratio (NLR) were significantly higher in the patients with coronary thrombus than in those without coronary thrombus (6.1 ± 1.1 vs 5.1 ± 1.3 mm, P < .001 and 3.4 ± 0.9 vs 2.5 ± 0.7, P < .001, respectively) and in the patients with no-reflow compared to patients with reflow. The EAT thickness was found to be correlated positively with the degree of the thrombus burden, NLR, and waist circumference and negatively with high-density lipoprotein cholesterol. Multivariate logistic regression analysis demonstrated that EAT thickness and NLR independently predicted coronary thrombus formation and no-reflow. We have suggested that EAT can play an important role in the pathophysiology of coronary thrombus formation and the no-reflow.